Relative age effects in sport. International perspectives (Routledge, 2020)
Individual achievement in sport is often constrained by an athlete`s age relative to the peers with whom they participate. A common practice within sport and educational domains is to group youth based on their chronological ages to help promote equal competition, age appropriate instruction, and ensure participant safety. While well intended, such grouping practices can often advantage relatively older children, while disadvantaging those who are relatively younger within the same age cohort. These phenomena are known as Relative Age Effects (RAEs).